A Gamification Design Tool to Improve Design Quality - Grimm, Valentin (Proceedings of Mensch und Computer 2022)
This demo features a prototype of a software tool to guide developers through the process of gamification design. It shall improve gameful designs, especially in the scientific community, and make the process of gamification design more accessible for non-experts in the field. The main goal of this first version is to gain user feedback on its usefulness with respect to intuition of use, its documentation capabilities and collaboration.